Ethical Codes of Nursing and the Practical Necessity in Iran - M Sanjari; F Zahedi; B Larijani (Tehran University of Medical Sciences, 2008)
Nursing is a universal health care necessity. Nursing profession, similar to the other medical professions, is responsible to maintain public health promotion, prevent diseases, and also care and rehabilitate client, family and the soci¬ety. The inher-ent nature of nursing is respect for moral values and human rights. However, clinical ethical dilem¬mas occur for nurses at all levels, not always concerning patients. Although this is the primary area of concern, it is relevant to all areas of nursing practice and every aspect of their professional roles including research activity, education and management. The ethical codes of nursing, which set out the ethical behaviors expected of registered nurses, are considered indisputable with regard to nursing practice. There are some national codes in the world but the international code of ethics for nurses was first adopted by the International Council of Nurses. The current paper gives an overview of nursing ethics history, which will be followed by the study on the promotion and dissemination of the nursing ethical codes and guidelines. The concepts, topics and strategies of some codes will be stated in this paper. The present study also aims to emphasize nursing ethics in Iran. Despite the compiling of general and specific guidelines of biomedical research in Iran during recent decade, there have been limited activities on the issue of nursing codes of ethics. Iranian nurses should be educated and fully prepared to en-gage with ethical is¬sues in the field of nursing. Given the importance of sociocultural issues, it is necessary to compile nurs-ing codes of ethics according to Islamic culture of Iran